Development of Learning Tools for Manual Transmission Repair Competency Based on 4C Skills for Vocational High School Students - Simatupang, Reza; Abizar, Haris; Ikhsanudin, Ikhsanudin (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This research attempts to test the feasibility of 4C-based manual transmission repair competency learning devices and determine the improvement of student learning outcomes with the developed learning devices. This kind of study employs a Research and Development strategy. This development research is designed by following the 4D development steps. The results of the development research showed a learning device product for manual transmission repair competency with a score of 96.75%. Based on the results of the analysis, it is known that there is a significant increase in student learning outcomes in the aspects of knowledge, skills, and attitudes of practice through 4C. These findings support the notion that learning tools developed are very feasible to use and student learning outcomes have increased using these devices.